2011
DOI: 10.1007/s10509-011-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

New clues to the impact broadening mystery in radio recombination lines

Abstract: Problems where impact broadened radio recombination lines appeared narrower than predicted first showed up ∼ 40 years ago at frequencies below ∼ 3 GHz. But it was soon found that the observations could be explained by throwing out the uniform density models and replacing them with variable density ones. However, this problem re-appeared recently when a mysterious line narrowing above quantum numbers of (n, ∆n) = (202,8) was reported from sensitive observations of Orion and W51 near 6 GHz. Here it is demonstrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 25 publications
(41 reference statements)
2
28
0
Order By: Relevance
“…A broader coverage was carried out by Gordon and Sorochenko (2002) and radio recombination lines have been a valuable tool for many years for the purpose of studying the physical conditions inside galaxies (Gordon 2008). Using the frequency switching observing technique we have found evidence that the impact broadened linewidths of hydrogen recombination lines near 6 GHz appear to become much narrower than predicted at high quantum numbers, n > 200 (Bell 1997;Bell et al 2000;Bell et al 2011;Bell 2011). Although a possible explanation for this was suggested by Oks (2004), this was refuted by Griem (2005).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A broader coverage was carried out by Gordon and Sorochenko (2002) and radio recombination lines have been a valuable tool for many years for the purpose of studying the physical conditions inside galaxies (Gordon 2008). Using the frequency switching observing technique we have found evidence that the impact broadened linewidths of hydrogen recombination lines near 6 GHz appear to become much narrower than predicted at high quantum numbers, n > 200 (Bell 1997;Bell et al 2000;Bell et al 2011;Bell 2011). Although a possible explanation for this was suggested by Oks (2004), this was refuted by Griem (2005).…”
Section: Introductionmentioning
confidence: 89%
“…Although a possible explanation for this was suggested by Oks (2004), this was refuted by Griem (2005). It was later demonstrated by Bell (2011) that when observations at other radio frequencies were taken into account the line narrowing appeared to be correlated with the density of recombination lines in frequency space. More recently Hey (2012) has obtained results that may eventually provide a theoretical explanation for the discrepancies seen between what the impact broadening theories predict and what has been observed in these high-n Rydberg-Rydberg recombination spectra from Galactic HII regions.…”
Section: Introductionmentioning
confidence: 99%
“…Rood et al (1984) search they detected high-order RRLs from b H114 to q H178 , but did not address Stark broadening. Bell et al (2000Bell et al ( , 2011 observed high-order RRLs at 6 and 17.6 GHz using a novel frequency switching (FS) method. Mathematically, this method is equivalent to applying a finite difference-a discrete analog of differentiation-to the observed spectrum (Alexander & Gulyaev 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematically, this method is equivalent to applying a finite difference-a discrete analog of differentiation-to the observed spectrum (Alexander & Gulyaev 2012). In Bell et al (2000Bell et al ( , 2011, FS was applied to the same spectrum six times successively (a 6th order finite difference), which made their method increasingly insensitive to line broadening as the line width increased and exceeded the FS offset parameter. Alexander & Gulyaev (2012) demonstrate that the narrowing of RRLs reported by Bell et al (2000Bell et al ( , 2011 is apparent: their method effectively filtered out Stark broadening for  n 200.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation